2006
DOI: 10.1007/s11095-005-9258-5
|View full text |Cite
|
Sign up to set email alerts
|

Transport Kinetics of Iron Chelators and Their Chelates in Caco-2 Cells

Abstract: Caco-2 cells are useful in screening iron chelators and chelates and estimating bioavailabilities. Structure and distribution coefficients partially predict passive transport through Caco-2 monolayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…UGT substrates typically contain electrophilic acceptor groups such as aliphatic alcohols and phenols, amines, and sulfhydryl or carbonyl groups (Dutton, 1980;Shipkova and Wieland, 2005). UGT1A6 preferentially metabolizes phenols (Harding et al, 1988;Orzechowski et al, 1994;Tukey and Strassburg, 2000), favoring formation of the 3-O-glucuronide, which was identified and measured in earlier studies (Kontoghiorghes et al, 1990;Huang et al, 2006). The second deferiprone glucuronide form, detected in glucuronidation assays with specific UGTs (UGT1A6, 1A8, 1A9, and 1A10) and certain human tissues, has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UGT substrates typically contain electrophilic acceptor groups such as aliphatic alcohols and phenols, amines, and sulfhydryl or carbonyl groups (Dutton, 1980;Shipkova and Wieland, 2005). UGT1A6 preferentially metabolizes phenols (Harding et al, 1988;Orzechowski et al, 1994;Tukey and Strassburg, 2000), favoring formation of the 3-O-glucuronide, which was identified and measured in earlier studies (Kontoghiorghes et al, 1990;Huang et al, 2006). The second deferiprone glucuronide form, detected in glucuronidation assays with specific UGTs (UGT1A6, 1A8, 1A9, and 1A10) and certain human tissues, has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Although the long-term safety profile of deferiprone is well defined, the mechanism of and factors involved in its adverse effects, such as gastrointestinal disturbances, arthralgia, neutropenia, and agranulocytosis, are unclear (Agarwal et al, 1990;Taher et al, 2001;Ceci et al, 2002;Cohen et al, 2003;Franchini and Veneri, 2004), thus emphasizing the need to decipher the underlying mechanisms and factors involved in these adverse effects. Deferiprone has good bioavailability, but its clearance is accelerated by rapid biotransformation: approximately 85% of the drug is metabolized to a nonchelating (inactive) 3-O-glucuronide conjugate (Huang et al, 2006) by UDP-glucuronosyltransferases (UGTs). Of all of the known human UGTs, 12 were previously evaluated for deferiprone glucuronidation in a single study, which revealed that only UGT1A6 was capable of catalyzing the glucuronidation of deferiprone (Haverfield et al, 2005).…”
mentioning
confidence: 99%
“…Huang and collaborators (Huang et al 2006), using the Caco-2 cell model cultured on permeable membrane, demonstrated that DFO, CP20 and ICL670 were passively transported across the enterocyte cell monolayer with a membrane permeability modulated by the lipophilicity and the charge of the chelators (CP20 [ ICL670). The iron chelates [Fe(ICL670) 2 ] and [Fe(DFO)] were not transported across Caco-2 monolayers, while the [Fe(CP20) 3 ] chelate was able to cross the monolayer in both directions.…”
Section: Effect Of Iron Chelators On Iron Metabolismmentioning
confidence: 99%
“…Uptake and/or efflux information was appraised in parallel studies to obtain information on the individual kinetic process (Bourdet et al, 2006). In some cases, data may be obtained from identical Transwells that provide data in the various compartments at each time point (Huang et al, 2006). In other studies, repetitive sampling at various time points in the receiver compartment of the same Transwell with volume replacement was used.…”
Section: Discussionmentioning
confidence: 99%